Monitoring of polar organic compounds in fresh waters using the Chemcatcher passive sampler - Rosamund F.A. Robinson; Graham A. Mills; Gary R. Fones (MethodsX, 2023)
The monitoring of polar organic pollutants in surface water is now undertaken to fulfil a number of legislative requirements. Passive sampling is being frequently used for this purpose and includes the commercially available Chemcatcher device. This protocol is based on knowledge that has been acquired over the past ten years in the use of the Chemcatcher for monitoring a wide range of polar organic compounds in freshwater. It provides detailed procedures and guidelines of how to prepare the sampler in the laboratory, deploy and retrieve the device in the field (including water and sampling site measurements) and subsequent sample processing in the laboratory up to instrumental analysis. By end users adopting this standardized, systematic protocol it will help to ensure the reproducibility of their monitoring data. • Robust and detailed procedure for the sampling of polar pollutants in surface waters using the Chemcatcher passive sampler • A low cost, novel and versatile apparatus for deploying the Chemcatcher at riverine sites • Practical tips based on extensive experience of using the Chemcatcher are provided for end-users